Photo-induced chemical reaction of trans-resveratrol. (15th March 2015) - Zhao, Yue; Shi, Meng; Ye, Jian-Hui; Zheng, Xin-Qiang; Lu, Jian-Liang; Liang, Yue-Rong
Highlights: The photo-induced chemical reaction of trans -resveratrol occurs in solution. Two major photoproducts are successively generated. Singlet oxygen reaction is a principal process at low level of trans -resveratrol. A new compound, 2-(4-hydroxyphenyl)-5, 6-benzofurandione, is identified. Abstract: Photo-induced chemical reaction of trans -resveratrol has been studied. UV B, liquid state and sufficient exposure time are essential conditions to the photochemical change of trans -resveratrol. Three principal compounds, cis -resveratrol, 2, 4, 6-phenanthrenetriol and 2-(4-hydroxyphenyl)-5, 6-benzofurandione, were successively generated in the reaction solution of trans -resveratrol (0.25 mM, 100% ethanol) under 100 μW cm −2 UV B radiation for 4 h. cis -Resveratrol, originated from isomerization of trans -resveratrol, resulted in 2, 4, 6-phenanthrenetriol through photocyclisation reaction meanwhile loss of 2 H. 2, 4, 6-Phenanthrenetriol played a role of photosensitizer producing singlet oxygen in the reaction pathway. The singlet oxygen triggered [4+2] cycloaddition reaction of trans -resveratrol, and then resulted in the generation of 2-(4-hydroxyphenyl)-5, 6-benzofurandione through photorearrangement and oxidation reaction. The singlet oxygen reaction was closely related to the substrate concentration of trans -resveratrol in solution.